Regenerated aramid fiber composite fabric and preparation process thereof
By cutting and cleaning the body armor, controlling the content of styrene block copolymer, and combining flame retardant coatings, the problem of waste of resources and degradation of performance during the regeneration of the body armor fiber is solved, and regeneration with high strength and good protective effects is achieved Aramid composite fabric.
Patent Information
- Application Number
- CN202411515412.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult for existing body armor to effectively separate and reuse their fibers after use, resulting in waste of resources and environmental pollution. At the same time, the residue of styrene block copolymers during the fiber regeneration process affects the strength and protective performance of the fibers.
By cutting the bulletproof vest into blocks and cleaning, the content of styrene block copolymer is controlled at ≤6%, and N,N-dimethylformamide or acetone is used as the washing liquid, combined with flame retardant coating to enhance The strength and protective properties of the fiber form a recycled aramid composite fabric.
It effectively improves the strength and protection effect of recycled aramid fibers, improves the mechanical properties and flame retardant properties of the fabric, reduces the damage of the fibers, and promotes the combination between the fibers, extending the service life of the fabric.
Abstract
Description
Technical Field
[0001] The present application relates to the field of aramid fibers, and in particular to a regenerated aramid composite fabric and a preparation process thereof. Background Art
[0002] The bulletproof vest is mainly composed of a cover, a bulletproof layer, a buffer layer, and a bulletproof plate.
[0003] The cover is usually made of chemical fiber fabric or wool-cotton fabric, which protects the bulletproof layer and makes the appearance beautiful. Some covers are equipped with several pockets to carry ammunition and other supplies. The bulletproof layer usually contains strong fibers, such as aramid fibers, to deflect or embed penetrating bullets or explosive fragments.
[0004] Bulletproof vests are usually treated as waste after use, which not only wastes resources but also may pollute the environment. The traditional method of disposing bulletproof vests is to discard them as a whole or simply physically crush them, without effectively separating and reusing the fibers in the bulletproof vests. Summary of the invention
[0005] In order to recycle the fibers in bulletproof vests, the present application provides a regenerated aramid composite fabric and a preparation process thereof.
[0006] The present application provides a recycled aramid composite fabric and a preparation process thereof using the following technical solutions: In the first aspect, the present application discloses a recycled aramid composite fabric, including the following technical solutions: A regenerated aramid composite fabric, comprising aramid regenerated fibers, wherein the aramid regenerated fibers are prepared by the following method: cutting a bulletproof vest fabric to obtain a block-shaped processed product containing a styrene block copolymer, washing the block-shaped processed product to reduce the attached styrene block copolymer, and drying the block-shaped processed product after washing to obtain the aramid regenerated fibers; The content of styrene block copolymer in the aramid regenerated fiber is ≤6%.
[0007] By adopting the above technical scheme, the bulletproof vest is obtained by bonding bulletproof layers layer by layer, and a lot of styrene block copolymers are attached to the surface of the block-shaped processed object obtained by cutting. The styrene block copolymer is a synthetic polymer material composed of styrene, isoprene and styrene monomers arranged alternately in a block structure, and has elasticity and resilience, as well as high viscosity. However, the presence of too much styrene block copolymer makes the aramid fiber too tough, and makes the aramid fibers adhere together, making it difficult to separate, and tensile deformation occurs during weaving, and it is difficult to restore to a natural state. Therefore, it is difficult to obtain fabrics by directly weaving the recycled aramid fibers, and the performance is reduced, affecting subsequent use; the recycled bulletproof vest is cut and washed, so that the styrene block copolymers on the surface of the aramid fibers are removed, and the content of the styrene block copolymers is controlled within the above range, which can effectively improve the strength of the obtained aramid fibers, and the residual styrene block copolymers can increase the roughness of the contact surface of the aramid regenerated fibers, thereby providing additional resistance and friction, and further improving the protective effect of the fabrics prepared subsequently.
[0008] Preferably, when the block-shaped processed object is cleaned, the following steps are included: The washing liquid is heated, and the block-shaped processed material is immersed in the heated washing liquid for washing for 10-15 minutes. The block-shaped processed material is then separated, dehydrated, and then washed again with new washing liquid to complete the washing.
[0009] By adopting the above technical scheme, the cleaning time when cleaning the block-like processed material is preferably controlled, the retention amount of styrene block copolymers in the block-like processed material can be effectively controlled, and the damage to the fiber during cleaning is reduced to further improve the overall strength of the fiber. At the same time, after the second washing, the decomposition effect of the styrene block copolymer can be further improved, and the washing effect on the system can be improved to further reduce the amount of debris retained on the fiber surface.
[0010] Preferably, the washing liquid comprises any one of N,N-dimethylformamide or acetone.
[0011] By adopting the above technical scheme, N,N-dimethylformamide is an organic compound and also an excellent solvent with a wide range of uses. After using N,N-dimethylformamide to clean the block-like processed material, the impurities and styrene block copolymer on the surface of the block-like processed material can be further dissolved and cleaned without damaging the fiber, thereby improving the cleaning effect; acetone has good solubility and dissolving power, and can also clean the impurities on the surface of the block-like processed material, thereby improving the strength of the aramid regenerated fiber.
[0012] Preferably, the washing liquid is heated to a temperature of 68-72°C.
[0013] By adopting the above technical solution, the temperature of the washing liquid is preferably within the above range, which can further improve the solubility of the washing liquid, so that the washing liquid can obtain just the right decontamination performance, and improve the activity of the washing liquid, and further improve the binding performance between the washing liquid and the block-shaped processed object, thereby promoting the cleaning performance of the block-shaped processed object.
[0014] Preferably, the resin content in the bulletproof vest fabric is 20-50wt%.
[0015] Preferably, a polyethylene terephthalate film is also provided on the surface of the bulletproof vest fabric.
[0016] Preferably, the regenerated aramid composite fabric also includes flame-retardant fibers, which include phenolic fibers and a flame-retardant layer. The flame-retardant layer is formed by attaching a flame-retardant coating to the surface of the phenolic fibers, and the flame-retardant coating includes chitosan, gelatin, phytic acid and phosphorous acid.
[0017] By adopting the above technical scheme, the aramid regenerated fiber is compounded with the flame-retardant fiber, and the fabric prepared by spinning has good mechanical properties and protective effects, and has significant flame retardant properties. After the surface of the flame retardant fiber substrate is coated with the flame retardant coating, a layer of flame retardant coating is formed on the surface of the flame retardant fiber substrate, thereby further improving the overall flame retardant properties of the flame retardant fiber substrate. At the same time, the overall stability of the flame retardant fiber substrate and the bonding performance with the aramid regenerated fiber can be effectively improved, and the comprehensive performance of the prepared fabric is further improved. After combining chitosan, gelatin, phytic acid and phosphorous acid, the adhesion performance on the surface of phenolic fiber can be improved, thereby improving the stability of the flame retardant coating. At the same time, phytic acid also contains phosphorus, which can synergistically improve the flame retardant properties of the flame retardant coating with phosphorous acid, thereby improving the flame retardant properties of the flame retardant fiber.
[0018] Preferably, the flame retardant coating is prepared by the following method: Chitosan is mixed with water, and phosphorous acid solution is added after magnetic stirring. The stirring is continued until the chitosan is dissolved, and a mixture is obtained after standing. Gelatin is added to the mixture under water bath conditions, and the mixture is stirred until the gelatin is dissolved. After the system is cooled, phytic acid is added, and the flame retardant coating is obtained after stirring.
[0019] By adopting the above technical scheme, chitosan and gelatin can release non-flammable gases such as nitrogen, ammonia and water vapor when heated to dilute combustible gases and oxygen, and form an expanded carbon layer on the surface of phenolic fiber. The polyphosphoric acid formed by the thermal decomposition of phytic acid can further catalyze the carbonization reaction of chitosan, gelatin and phenolic fiber to form a more solid and compact carbon layer, organize the transfer of heat and oxygen, and further improve the flame retardant properties of the flame retardant fiber.
[0020] Preferably, the mass ratio of chitosan, phytic acid and gelatin is 1:1.5:(0.6-0.7).
[0021] By adopting the above technical solution, preferably the mass ratio of chitosan, gelatin and phytic acid is within the above range, which can further improve the stability and flame retardant performance of the flame retardant coating.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. After cutting the bulletproof vest, a block-shaped processed product containing aramid fiber and styrene block copolymer is obtained. After washing the block-shaped processed product, the glue on the surface of the aramid fiber is removed, and the obtained aramid regenerated fiber can be used to prepare fabrics. At the same time, the strength of the obtained aramid regenerated fiber is further improved. A certain amount of styrene block copolymer remains on the surface of the aramid regenerated fiber, so that the strength of the aramid regenerated fiber is improved, and the residual styrene block copolymer can increase the roughness of the contact surface of the aramid regenerated fiber, thereby increasing the additional resistance and friction, and then improving the protective effect of the fabric prepared subsequently. The treated aramid regenerated fiber is composited with the flame-retardant fiber to prepare a fabric with good mechanical properties and flame-retardant properties; 2. Optimizing the washing temperature, washing time and washing liquid for the block-like processed material can effectively improve the washing effect of the block-like processed material, and at the same time can further improve the control of the residual amount of styrene block copolymer to improve the stability of the aramid regenerated fiber; 3. The flame-retardant fiber is prepared by combining phenolic fiber with a flame-retardant coating. After chitosan, gelatin, phytic acid and phosphorous acid in the flame-retardant coating are combined, the adhesion performance on the surface of the phenolic fiber can be improved, thereby improving the stability of the flame-retardant coating. At the same time, phytic acid also contains phosphorus, which can synergistically improve the flame-retardant properties of the flame-retardant coating with phosphorous acid, thereby improving the flame-retardant properties of the flame-retardant fiber. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained from commercial sources; among them, Example 1 Preparation of aramid regenerated fiber: Waste bulletproof vest fabrics are cut to obtain block-shaped processed products of equal size containing styrene block copolymers, the washing liquid is heated to 68°C, washed for 15 minutes, and then the block-shaped processed products of the first washing are separated and dehydrated for 3 minutes. After dehydration, the block-shaped processed products are added to new washing liquid for secondary washing, and after washing for 15 minutes, the washing is completed by dehydration; the washed processed products are dried at 60°C for 4 hours to obtain aramid regenerated fibers, and the styrene block copolymer content of the aramid regenerated fibers is 1%.
[0024] The resin content of the waste bulletproof vest fabric is 20wt%, and the surface does not contain a polyethylene terephthalate film; the washing liquid is prepared by mixing N,N-dimethylformamide and deionized water in a mass ratio of 1:16.
[0025] Preparation of flame retardant coatings: 9.68 g of chitosan was mixed with 250 mL of deionized water, and a chitosan dispersion was obtained after magnetic stirring. The chitosan dispersion was added to 80 mL of 1 mol / L phosphorous acid solution, and the chitosan was completely dissolved by magnetic stirring. The mixture was allowed to stand for 1 hour to obtain a mixed solution. The mixture was heated to 60°C in a water bath, and then 5.8 g of gelatin was added. The gelatin was completely dissolved by magnetic stirring. The mixture was then naturally cooled for 1 hour, 14.52 g of phytic acid was added, and the mixture was stirred for 2 hours to obtain a flame retardant coating.
[0026] Preparation of flame retardant fibers: The aramid fiber was immersed in the flame retardant coating, heated to 45°C and allowed to stand for 3 hours, taken out, and dried in a drying oven at 60°C for 3 hours to obtain the flame retardant fiber.
[0027] Preparation of recycled aramid composite fabric with adhesive: 25% flame retardant fiber, 10% aramid regenerated fiber and the rest are common aramid fibers, and the blended fabric is obtained. The temperature of the grey fabric is raised to 200°C, and the grey fabric is dried and shaped at a drying speed of 24Y / min. After the drying is completed, a regenerated aramid composite fabric is obtained.
[0028] Example 2 Preparation of aramid regenerated fiber: Waste bulletproof vest fabrics are cut to obtain block-shaped processed products of equal size containing styrene block copolymers, the washing liquid is heated to 72°C, washed for 10 minutes, and then the block-shaped processed products of the first washing are separated and dehydrated for 5 minutes. After dehydration, the block-shaped processed products are added to new washing liquid for secondary washing, and after washing for 10 minutes, the washing is completed by dehydration; the washed processed products are dried at 60°C for 4 hours to obtain aramid regenerated fibers, and the styrene block copolymer content of the aramid regenerated fibers is 6%.
[0029] The resin content of the waste bulletproof vest fabric is 50wt%, and the surface contains a polyethylene terephthalate film; the washing liquid is prepared by mixing acetone and deionized water in a mass ratio of 1:16.
[0030] Preparation of flame retardant coatings: 9.38 g of chitosan was mixed with 250 mL of deionized water, and a chitosan dispersion was obtained after magnetic stirring. The chitosan dispersion was added to 80 mL of 1 mol / L phosphorous acid solution, and the chitosan was completely dissolved by magnetic stirring. The mixture was allowed to stand for 1 hour to obtain a mixed solution. The mixture was heated to 60°C in a water bath, and then 6.56 g of gelatin was added and magnetic stirring was performed to completely dissolve the gelatin. The mixture was then naturally cooled for 1 hour, 14.06 g of phytic acid was added, and the mixture was stirred for 2 hours to obtain a flame retardant coating.
[0031] Preparation of flame retardant fibers: The aramid fiber was immersed in the flame retardant coating, heated to 45°C and allowed to stand for 3 hours, taken out, and dried in a drying oven at 60°C for 3 hours to obtain the flame retardant fiber.
[0032] Preparation of recycled aramid composite fabric with adhesive: 25% flame retardant fiber, 20% aramid regenerated fiber and the rest are common aramid fibers, and the blended fabric is obtained. The temperature of the grey fabric is raised to 200°C, and the grey fabric is dried and shaped at a drying speed of 24Y / min. After the drying is completed, a recycled aramid composite fabric is obtained.
[0033] Example 3 Preparation of aramid regenerated fiber: Waste bulletproof vest fabrics are cut to obtain block-shaped processed products of equal size containing styrene block copolymers, the washing liquid is heated to 70°C, washed for 13 minutes, and then the block-shaped processed products after the first washing are separated and dehydrated for 5 minutes. After dehydration, the block-shaped processed products are added to new washing liquid for secondary washing. After washing for 13 minutes, the washing is completed by dehydration; the washed processed products are dried at 60°C for 4 hours to obtain aramid regenerated fibers, and the styrene block copolymer content of the aramid regenerated fibers is 3.5%.
[0034] The resin content of the waste bulletproof vest fabric is 35%, and the surface contains a polyethylene terephthalate film; the washing liquid is prepared by mixing N,N-dimethylformamide and deionized water in a mass ratio of 1:16.
[0035] Preparation of flame retardant coatings: 9.52 g of chitosan was mixed with 250 mL of deionized water, and a chitosan dispersion was obtained after magnetic stirring. The chitosan dispersion was added to 80 mL of 1 mol / L phosphorous acid solution, and the chitosan was completely dissolved by magnetic stirring. The mixture was allowed to stand for 1 hour to obtain a mixed solution. The mixture was heated to 60°C in a water bath, and then 6.19 g of gelatin was added. The gelatin was completely dissolved by magnetic stirring. The mixture was then naturally cooled for 1 hour, 14.29 g of phytic acid was added, and the mixture was stirred for 2 hours to obtain a flame retardant coating.
[0036] Preparation of flame retardant fibers: The aramid fiber was immersed in the flame retardant coating, heated to 45°C and allowed to stand for 3 hours, taken out, and dried in a drying oven at 60°C for 3 hours to obtain the flame retardant fiber.
[0037] Preparation of recycled aramid composite fabric with adhesive: 25% flame retardant fiber, 20% aramid regenerated fiber and the rest are common aramid fibers, and the blended fabric is obtained. The temperature of the grey fabric is raised to 200°C, and the grey fabric is dried and shaped at a drying speed of 24Y / min. After the drying is completed, a recycled aramid composite fabric is obtained.
[0038] Example 4 Example 4 is based on Example 3. The washing liquid in Example 4 is prepared by mixing sodium benzenesulfonate (CAS No.: 515-42-4), laureth-4 (CAS No.: 68439-50-9) and deionized water in a mass ratio of 0.5:0.5:8.
[0039] Example 5 Example 5 is based on Example 3, and the washing liquid in Example 5 is heated to 80°C.
[0040] Example 6 Example 6 is based on Example 3, and the washing liquid in Example 6 is heated to 60°C.
[0041] Example 7 Example 7 is based on Example 3, and the two cleaning times of the block-shaped processed objects in Example 7 are both 20 minutes.
[0042] Example 8 Example 8 is based on Example 3, and the two cleaning times of the block-shaped processed objects in Example 8 are both 5 minutes.
[0043] Example 9 Example 9 is based on Example 3, and the content of styrene block copolymer in the aramid regenerated fiber in Example 9 is 8%.
[0044] Example 10 Example 10 is based on Example 3. In Example 10, the amount of chitosan added to the flame retardant coating is 10.34 g, the amount of gelatin added is 4.14 g, and the amount of phytic acid added is 15.52 g.
[0045] Embodiment 11 Example 11 is based on Example 3. In Example 11, the amount of chitosan added to the flame retardant coating is 8.82 g, the amount of gelatin added is 7.94 g, and the amount of phytic acid added is 13.24 g.
[0046] Example 12 Example 12 is based on Example 3, and only phosphorous acid is added to the flame retardant coating in Example 12.
[0047] Comparative Example 1 Comparative Example 1 is based on Example 3, and the block-shaped processed material is not cleaned in Comparative Example 1.
[0048] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the flame retardant coating is not coated on the surface of the phenolic fiber.
[0049] The following performance tests were performed on the samples of Examples 1-12 and Comparative Examples 1-2: (1) Flame retardant performance test The flame retardant performance of the samples was tested based on "GB / T5454 1997 Textile Combustion Performance Test Oxygen Index Method". The sample fabric was cut into a size of 1.5cm×2cm and then the limiting oxygen index was tested. Each sample was tested three times, and the average value was taken. The test results are recorded in Table 1, where the larger the limiting oxygen index, the better the flame retardant effect.
[0050] (2) Strength performance test According to GB / T14343 2008, the sample fabric was cut into a size of 1.5 cm × 2 cm and then tested for breaking strength. Each sample was tested three times, and the average value was taken. The test results are recorded in Table 1. The higher the breaking strength, the better the mechanical properties of the fabric.
[0051] Table 1 Performance test results of samples of Examples 1-12 and Comparative Examples 1-2 Test specimen Polar oxygen index / % Breaking strength / N Example 1 36 378 Example 2 37 376 Example 3 39 380 Example 4 32 355 Example 5 33 360 Example 6 33 362 Example 7 32 360 Example 8 32 358 Example 9 27 301 Example 10 26 355 Embodiment 11 25 356 Example 12 20 350 Comparative Example 1 22 331 Comparative Example 2 17 354 Data analysis Combined with Table 1, it can be seen that the polar oxygen index of Examples 1-3 is 36% or above, indicating that the recycled aramid composite fabric with glue prepared in the present application has good flame retardant properties; the breaking strength of Examples 1-3 is 370N or above, indicating that the recycled aramid composite fabric with glue prepared in the present application has good strength and protection properties.
[0052] The washing liquid in Example 4 is sodium benzene sulfonate and laureth-4, and the solubility of the styrene block copolymer on the surface of the block treated material is poor, making it difficult to further clean the aramid fiber. The residual amount of the styrene block copolymer is large, and the washing effect of other organic matter is difficult to further improve. Therefore, the stability of the aramid regenerated fiber is reduced, and the performance of Example 4 is reduced.
[0053] The washing temperatures of the block-like processed materials in Examples 5 and 6 are not within the range specified in the present application. When the washing temperature is too low, the solubility of the washing liquid is difficult to further improve, the activity of the washing liquid is reduced, and the bonding effect with the block-like processed materials is difficult to further improve, so the washing effect is reduced. When the washing temperature is too high, the properties of the aramid fiber itself will be destroyed, thereby reducing the various properties of the prepared aramid regenerated fiber, and the bonding effect with the flame-retardant fiber is difficult to further improve. Therefore, the performance of Examples 5 and 6 is reduced.
[0054] The washing time for washing the block-like processed material in Examples 7 and 8 is not within the range specified in the present application. When the washing time is too long, the bonding performance between the residual styrene block copolymer and the aramid regenerated fiber is easily reduced, thereby affecting the comprehensive performance of the aramid regenerated fiber. When the washing time is too short, the washing effect of the washing liquid on the block-like processed material is difficult to be further improved, and other impurities are attached to the surface of the obtained aramid regenerated fiber, affecting the comprehensive performance of the aramid regenerated fiber. Therefore, the performance of Examples 7 and 8 is reduced.
[0055] In Example 9, the content of styrene block copolymer is greater than 6%. When the styrene block copolymer content of the aramid regenerated fiber is too much, the excessive styrene block copolymer will make the toughness of the aramid regenerated fiber too large, the fiber content of the aramid regenerated fiber decreases, and it is difficult to weave, and it is difficult to further improve the strength of the aramid regenerated fiber, and the overall performance of the fabric is seriously reduced.
[0056] The addition amounts of chitosan, gelatin and phytic acid in Example 10 and Example 11 are not within the range specified in the present application. When the addition amount of gelatin is too much or too little, it will affect the overall stability of the flame retardant coating, and the bonding performance with the phenolic fiber will also decrease, thereby reducing the flame retardant performance of the flame retardant fiber.
[0057] The flame retardant filler in Example 12 contains only phosphorous acid. It is difficult to further improve the flame retardant properties of the prepared flame retardant layer only by phosphorous acid and phenolic fiber. At the same time, the bonding performance between the flame retardant coating and the phenolic fiber is difficult to be further improved, so the performance of Example 12 is reduced.
[0058] In Comparative Example 1, the block-shaped processed material was not cleaned, but only crushed and composited with the flame-retardant fiber. The bonding property of the obtained regenerated aramid composite fabric was seriously reduced, and the stability of the prepared fabric was affected, so the performance of Comparative Example 1 was reduced.
[0059] In Comparative Example 2, no flame retardant coating is coated on the surface of the phenolic fiber. The flame retardant properties of the phenolic fiber not coated with the flame retardant coating are difficult to further improve, and the protective effect on the phenolic fiber is significantly reduced, thereby affecting the comprehensive performance of the prepared fabric. Therefore, the performance of Comparative Example 2 is reduced.
[0060] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A recycled aramid composite fabric, characterized in that: The invention comprises aramid regenerated fiber, wherein the aramid regenerated fiber is prepared by the following method: After cutting the bulletproof vest fabric, a block-shaped processed product containing styrene block copolymer is obtained, the block-shaped processed product is cleaned to reduce the attached styrene block copolymer, and after cleaning, the block-shaped processed product is dried to obtain aramid regenerated fiber; The content of styrene block copolymer in the aramid regenerated fiber is ≤6%.
2. The regenerated aramid composite fabric according to claim 1, characterized in that: When the block-shaped processed object is cleaned, the following steps are included: The washing liquid is heated, and the block-shaped processed material is immersed in the heated washing liquid for washing for 10-15 minutes. The block-shaped processed material is then separated, dehydrated, and then washed again with new washing liquid to complete the washing.
3. The regenerated aramid composite fabric according to claim 2, characterized in that: The washing liquid includes any one of N,N-dimethylformamide or acetone.
4. The regenerated aramid composite fabric according to claim 2, characterized in that: The washing liquid is heated to a temperature of 68-72°C.
5. The regenerated aramid composite fabric according to claim 2, characterized in that: The resin content in the bulletproof vest fabric is 20-50wt%.
6. The regenerated aramid composite fabric according to claim 1, characterized in that: The surface of the bulletproof vest fabric is also provided with a polyethylene terephthalate film.
7. The regenerated aramid composite fabric according to claim 1, characterized in that: The regenerated aramid composite fabric also includes flame-retardant fibers, which include phenolic fibers and a flame-retardant layer. The flame-retardant layer is formed by attaching a flame-retardant coating to the surface of the phenolic fibers. The flame-retardant coating includes chitosan, gelatin, phytic acid and phosphorous acid.
8. The regenerated aramid composite fabric according to claim 7, characterized in that: The flame retardant coating is prepared by the following method: Chitosan is mixed with water, and phosphorous acid solution is added after magnetic stirring. The stirring is continued until the chitosan is dissolved, and a mixture is obtained after standing. Gelatin is added to the mixture under water bath conditions, and the mixture is stirred until the gelatin is dissolved. After the system is cooled, phytic acid is added, and the flame retardant coating is obtained after stirring.
9. The regenerated aramid composite fabric according to claim 8, characterized in that: The mass ratio of chitosan, phytic acid and gelatin is 1:1.5:(0.6-0.7).
10. A method for preparing a regenerated aramid composite fabric according to claim 1, characterized in that: The steps include: Aramid regenerated fiber, common aramid fiber, flame retardant fiber and polyester fiber are blended to obtain grey cloth, the grey cloth is heated, and the grey cloth is dried and shaped. After drying, a regenerated aramid composite fabric is obtained.
Citation Information
Patent Citations
Flame-retardant and fireproof fabric, and processing technology and textile thereof
CN103352293A
Method for utilizing waste bulletproof helmet to prepare aramid pulp
CN108219190A
Method for recovering aramid fiber from aramid fiber / phenolic resin composite material
CN109836610A
Motor vehicle interior flame-retardant fabric
CN113046890A
Flame-retardant fabric
CN114775280A
